2017
DOI: 10.1177/1457496917738922
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Renal Cell Carcinoma Extending Into Venous System: A 20-Year Experience

Abstract: Our novel classification system can be used to select the optimal surgical approach and method for patients with renal cell carcinoma and venous thrombus. Its use is associated with prolonged survival and relatively few complications. Metastasis is an independent risk factor of overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
9
0
2
Order By: Relevance
“…Metastasis at surgery was generally reported as a poor prognostic indicator in patients with RCC with VTT [ 17 , 27 ], with a median survival expectation of less than 1 year. However, some studies found inconsistent outcomes [ 14 , 28 ], even some patients with metastatic diseases have prolonged survival due to unknown reasons [ 6 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis at surgery was generally reported as a poor prognostic indicator in patients with RCC with VTT [ 17 , 27 ], with a median survival expectation of less than 1 year. However, some studies found inconsistent outcomes [ 14 , 28 ], even some patients with metastatic diseases have prolonged survival due to unknown reasons [ 6 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some believed the presence of IVC tumor thrombus affected the prognosis with poor prognosis, [15] while others believed that tumor thrombus had little effect on prognosis. [16,17]…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical techniques and perioperative management have been improved a lot over time, the overall survival of patients with RCC and VTT remains poor, with 5-year OS varied from 37-71% [8,[12][13][14][15][16]. This wide variation may result from varied sample size, VTT level, surgical era, tumor pathological classi cation, comorbidities of patient population and improvements in adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis at surgery was generally reported as a poor prognostic indicator in patients with RCC with VTT [16,24], with a median survival expectation of less than 1 year. However, some studies found inconsistent outcomes [13,27], even some patients with metastatic diseases have prolonged survival due to unknown reasons [6,28].…”
Section: Discussionmentioning
confidence: 99%